Penguatan Pendidikan Karakter Berbasis Islamic Action Theory untuk Meningkatkan Daya Juang dan Ketahanan Moral Guru: Strengthening Character Education Based on Islamic Action Theory to Enhance Teacher Perseverance and Moral Resilience - Yelfiza Yelfiza; Yulmiati Yulmiati; Melvina Melvina; Rani Autila (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This community service program aimed to strengthen teachers’ understanding and awareness of character education through the Islamic Action Theory (IAT) approach, particularly in developing action awareness, perseverance, and moral resilience in professional practice. The program was initiated to reinforce teachers’ internal dimensions in interpreting values, professional ethics, and the consistency of intention in pedagogical activities. The activity was conducted in the form of a socialization program designed to provide conceptual reinforcement regarding Islamic Action Theory, professional reflection, and their relevance to moral awareness in educational actions. The methods included material presentation, interactive discussions, and exploration of participants’ professional experiences. The implementation indicated that the program provided a reflective space for teachers to reexamine their professional practices, particularly in self-reflection, intention alignment, and the interpretation of values in pedagogical actions. Teachers began to perceive reflection not merely as an evaluative activity but as an essential mechanism for strengthening professional awareness, perseverance, and moral resilience in responding to the dynamics of educational practice. This program represents an initial step toward supporting the reinforcement of character education, based on action awareness and integrated with moral and spiritual values. The program is expected to serve as a foundation for further practical and sustainable activities.